(untitled) (Letras & Letras, 2024)
The main theses of the Bakhtin Circle reflect and refract the conceptual apparatus of the Russian formalists when it comes to the perception of the aesthetical object. This article aims to foster a theoretical dialogue between the groups of thinkers by comparing the theses on the specificity of literature from both Russian Formalism and the Bakhtinian perspective. The goal is to discuss philosophical-conceptual tensions related to the perception of the aesthetic object and the consequent linguistic shaping in both currents mentioned. We address the pre-sensible perception in Merleau-Ponty’s (2014) thought and approach the concepts of estrangement and isolation from the perspectives of formalism, by Chklóvski (2013) and coleagues, and dialogism, focusing Bakhtin’s (1998; 2023) former texts. While both schools of thought agree on the role of artistic objects in renewing perceptions of the world, their differing understandings of language suggest distinct roles for the poet in relation to the object/character and the axiological universe.